Influence of Incubation Temperature and Relative Humidity on the Egg Hatchability Pattern of Two-Spotted (Gryllus bimaculatus) and House (Acheta domesticus) Crickets - J. Mitchaothai; Rachakris Lertpatarakomol; Tassanee Trairatapiwan; Achara Lukkananukool (Animals, 2024)
) crickets. Experiment I involved 100 cricket eggs per hatching box for each species, with six replications for each controlled incubation temperature of 23, 25, 27, 29, 30, 31, 32, and 33 °C at 70% RH. Experiment II used all the same procedures as Experiment I, except for incubation temperatures of 29, 30, 31, and 32 °C tested with varied RH levels of 65%, 70%, and 75%. In Experiment I, two-spotted crickets (9.47 ± 1.99 days) exhibited faster hatching than house crickets (13.70 ± 2.78 days). Additionally, the onset of hatching decreased with higher incubation temperatures for both types of crickets. In Experiment II, an incubation temperature of 31 °C and 70% RH resulted in a hatching rate of 79.75% for two-spotted crickets, with hatching beginning in 6 days. For house cricket eggs, the optimal conditions of 30 °C and 65-75% RH led to a peak daily hatching rate of 62.00-65.50% and hatching onset in 12 days. Thus, this study established the optimal incubation temperature and RH for egg hatching of two-spotted and house crickets.
Keywords: Insect Utilization and Effects; Insect and Arachnid Ecology and Behavior; Animal and Plant Science Education